A Series of 35 Cutaneous Infections Caused by Mycobacterium marinum in Han Chinese Population - Wenjie Chen; Fangfang Bao; Qing Pan; Tingting Liu; Xiaotong Xue; Hong Liu; Furen Zhang (Journal of Tropical Medicine)
Cutaneous Mycobacterium marinum infection is an increasingly infectious disease presenting unique diagnostic and therapeutic challenges. The aim of this study was to evaluate the differences in time to treatment among patients with different types of skin lesions and who were treated with single or multidrug therapies. In addition, the clinical characteristics of M. marinum infection were explored and the mechanism of the host immune responses was investigated. The electronic medical records of 35 patients with M. marinum infection were reviewed. The clinical characteristics, histopathological and laboratory data, and treatment outcomes were analyzed. Immunohistochemical analysis was performed to clarify the immune mechanisms induced by M. marinum infection in 9 patients and 5 healthy controls. Of the 35 patients, 25 (71.4%) had lesions with sporotrichoid patterns. The duration of patients with sporotrichoid lesions or treatment with multiple drugs was longer, although differences were not significant, possibly due to the small cohort. However, this trend was also observed in previous studies, making it worthy of further attention. Expression levels of cytokines (IFN-γ, IL-4, IL-9, and FOXP3) were significantly upregulated in the patient specimens, whereas there were no significant differences in IL-17 and IL-22 expression levels between the patient and control groups.